Molecular analysis of hobo and Himar 1 transposition - Lipkow, K; Lipkow, Karen (2003)
The aim of this study is to find out more about how eukaryotic transposons work. Transposons are widespread genetic elements that can autonomously change their position within a genome. Their translocation is mediated by the transposase enzyme, encoded by the transposon itself. Transposition is often associated with mutations and recombination in the host and may promote evolutionary change. Most knowledge of the principles and molecular mechanisms has so far come from prokaryotic transposons. Eukaryotic transposons have mostly been studied on the level of population dynamics. In this thesis, I studied two eukaryotic transposons on a molecular level, hobo and Himarl are members of very widespread transposon families, hAT and mariner-like elements, respectively. Their interest lies mainly in the preposition that the order of catalytic steps is the opposite of all prokaryotic transposons studied so far. I developed several protocols for the purification of hobo transposase. These preparations were assayed by several methods in vitro. DNA hairpin structures, which had been postulated to arise in the flanking DNA upon hobo excision, were assayed for with a newly developed very sensitive method, frayed duplex PCR. Here, and in reconstructed in vivo transposition systems, no specific transpositional activity, apart from a high toxicity for the host cells, was detected. This suggests a requirement for as yet unidentified host factors. For Himarl, I improved the published transposase purification protocol and optimised the in vitro reaction conditions, achieving a c. 10-fold increase in specific activity. Specific transposase-DNA binding is shown, representing the earliest intermediates in transposition. Later complexes studied are target capture and strand transfer complexes, which are the final stage of the transposition reaction. Hydroxyradical footprinting and band shift assays suggest that Himarl transposase binds a single DNA end as multimers while occupying only a single DNA binding site. Himarl can bind and commit to target DNA before as well as after excision from the donor. Target commitment is only clearly visible under conditions of macromolecular crowding, and insertions were found to be more efficient if the target is supercoiled. These are both conditions closely resembling the situation in the eukaryotic nucleus.